An evaluation of a novel decision aid - mobile app in a shared decision making for patients in dentistry / Tong Wah Lim … [et al.] - Tong, Wah Lim; Abdul Adzim, Siti Nor Shaswani; Akbar, Maizatin Firah Akbar; Mustaza, Teh Adilla (UiTM Press, 2018)
The idea of Shared Decision Making (SDM) is well known in medical field but not well acknowledged in dental practices. It is an educational model for actively involving patients in clinical decision making process by providing patients with the best currently available clinical evidences regarding treatment outcomes, allowing for the clarification of patient and practitioner preferences. SDM need to be implemented effectively with the use of decision aids that provide evidence-based answers for patient questions and integrate the patient preferences. This study aimed to develop a novel Decision Aid – Mobile App (MA) for chairside used in the SDM process and to compare patients’ dental knowledge, satisfaction and anxiety level by using MA and Standard Care (SC). The MA was developed by mobile app designer and researchers. The MA provides an evidence-based prognoses, benefits, risks and costs for various treatment options based on review by a group of prosthodontists. Thirty-four (34) participants were selected to participate in this study. Subjects were randomly assigned into two groups which were SC (n=17) and MA (n=17). Questionnaire regarding knowledge, satisfaction and anxiety was answered by the subjects after the treatment options discussion in the students’ clinic. From the results of this study, 26 questionnaires (76.5%) were completely answered and included in the study. Subjects in the MA group (n=13) demonstrated a statistically significant increase in knowledge (chi-square test; p<0.05) compared to the SC group (n=13). However, there was no significant difference between two groups with regards to their anxiety and satisfaction level (Mann-Whitney U-test; p>0.05). This study reported that the use of novel mobile app as a decision aid play an important role to facilitate SDM process in clinical dentistry. The result has reported a significant improvement in patient knowledge of prosthodontic treatment options.